2009
DOI: 10.1051/0004-6361:200810862
|View full text |Cite
|
Sign up to set email alerts
|

On solar cycle predictions and reconstructions

Abstract: Context. Generally, there are two procedures for solar cycle predictions: the empirical methods -statistical methods based on extrapolations and precursor methods -and methods based on dynamo models. Aims. The goal of the present analysis is to forecast the strength and epochs of the next solar cycle, to investigate proxies for grand solar minima and to reconstruct the relative sunspot number in the Maunder minimum. Methods. We calculate the asymmetry of the ascending and descending solar cycle phases (Method … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
48
0

Year Published

2010
2010
2022
2022

Publication Types

Select...
8
2

Relationship

1
9

Authors

Journals

citations
Cited by 50 publications
(48 citation statements)
references
References 69 publications
0
48
0
Order By: Relevance
“…Hara (2009) analysed X-ray bright points observed by the Yohkoh soft X-ray telescope in the period 1994−1998. This time period starts close to the end of cycle 22 and ends soon after the beginning of cycle 23 (see Table 1 in Brajša et al 2009).…”
Section: Solar Rotation Profile and Rotation Velocity Residualsmentioning
confidence: 99%
“…Hara (2009) analysed X-ray bright points observed by the Yohkoh soft X-ray telescope in the period 1994−1998. This time period starts close to the end of cycle 22 and ends soon after the beginning of cycle 23 (see Table 1 in Brajša et al 2009).…”
Section: Solar Rotation Profile and Rotation Velocity Residualsmentioning
confidence: 99%
“…Is it a purely stochastic effect, or is it an example of deterministic chaos? Economists have long regarded the solar cycle as an example of stochastic behaviour, and Barnes, Sargent & Tryon (1980) showed that an Autoregressive Moving Average (ARMA) model (constructed by combining a three-term recurrence relation with filtered Gaussian noise) provided a very plausible representation of solar activity (see also Brajsa et al 2009). If we seek a more causal description, we may suppose that the cyclic dynamo is disturbed by fluctuations in the underlying hydrodynamics of the convection zone, which we can regard as random.…”
Section: Origins Of Aperiodic Modulationmentioning
confidence: 99%
“…While some methods provide predictions well in advance or close to the time of initiation of an upcoming SC, a few other methods offer step-by-step predictions as an SC advances. It has been shown that precursor methods show better performance compared with other prediction methods (Li et al 2001;Brajsa et al 2009). Some of the aforementioned methods are based on a physical approach (Dikpati & Charbonneau 1999;Schatten 2005;Dikpati et al 2006;Dikpati & Gilman 2008;Svalgaard et al 2005) rather than a strictly numerical approach.…”
Section: Introductionmentioning
confidence: 99%